2019
DOI: 10.29036/jots.v10i18.84
|View full text |Cite
|
Sign up to set email alerts
|

Assessing The Effect Of International Relations On Tourism Demand In The Context Of Turkey-Russia Aircraft Crisis

Abstract: The purpose of this research is to evaluate the effect of international relations on tourism demand in the context of aircraft crisis between Turkey and Russia that occurred on November 24, 2015. For this purpose, a document analysis has been carried out on tourist count and revenue before, during and after the crisis. It has been determined in the research that the Russian tourist count and tourism revenue during the crisis (2016=866.256 tourists, 76.26% decrease compared to 2015) remained significantly below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…According to Dolnicar (2007), the tourist's knowledge of the risks and precise perceptions regarding safety has a strong impact on travel decisions. If alternatives available involve risk, the decision-makers tend to delay or quit taking decisions concerned (Dhar, 1997;Tjiptono & Yang, 2018;Uslu & Akay, 2019). In a research paper conducted on online consumer behavior, Cho et al (2006) defined such a behavior involving delay in decision-making as hesitation by itself.…”
Section: Tourist Knowledge and Tourist Hesitationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Dolnicar (2007), the tourist's knowledge of the risks and precise perceptions regarding safety has a strong impact on travel decisions. If alternatives available involve risk, the decision-makers tend to delay or quit taking decisions concerned (Dhar, 1997;Tjiptono & Yang, 2018;Uslu & Akay, 2019). In a research paper conducted on online consumer behavior, Cho et al (2006) defined such a behavior involving delay in decision-making as hesitation by itself.…”
Section: Tourist Knowledge and Tourist Hesitationmentioning
confidence: 99%
“…Results of previous studies have identified certain factors that have considerable impact on tourists’ hesitation toward the decision of destination choices (Kogo et al, 2020 ; Nadeau et al, 2008 ; Polas et al, 2018 ; Um & Crompton, 1990 ; Uslu & Akay, 2019 ). Health, travel expenses, a distance of the destination, and time constraint significantly contributed to the tourists’ hesitation toward destination choice (Carvache-Franco et al, 2019 ; Shaktawat & Vadhera, 2020 ; Tepavčević et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…School travel plan (STP) may provide a significant source of physical activities and travel experience for students in many countries (Buttazzoni, Clark, Seabrook, & Gilliland, 2019; Deligianni, Papadoulis, Monsuur, Quddus, & Enoch, 2021; Jing, Wang, Chen, & Zha, 2018); the STP for graduation travel is an important market for travel agencies (Hinckson, 2016;Villanueva-Meyer et al, 2015;Wen et al, 2021); The plan was developed through collaboration among the school, community, and local tourism business (Deligianni et al, 2021;Jing et al, 2018;Mammen, Stone, Buliung, & Faulkner, 2015), tourism product advantage is an important condition for customers to choose the travel agency process. If travel agencies have innovative leadership or leading product advantages, there will be more opportunities to stand out among other competitors in choosing a cooperation process (Tari et al, 2020;Uslu & Akay, 2019). Travel agencies with the above capabilities will become a priority for customers to choose as the cooperative alliance.…”
Section: Introductionmentioning
confidence: 99%
“…Economists have pointed out in several cases that the level of government and corporate debt is becoming unsustainable, and the US-China trade war risks exacerbating these problems, but no one has been able to predict the adverse effects of the COVID-19 pandemic on the population and the world economy. Analysts (Cygler et al, 2018;Bencsik et al, 2019;Grossman, 2018;Lengyel et al, 2017;Mura et al, 2017;Olaniyi et al, 2019;Petcu, 2019;Popescu, G. H., Ciurlău, 2019;Raišienė et al, 2019;Rajiani et al, 2018;Sroka, Szanto, 2018;Trettin et al, 2019;Uslu, Akay, 2019;Veselitskaya et al, 2019;Zhuravleva et al, 2019;Ajaz Khan et al, 2019;Çelik, 2019;Duľová Spišáková et al, 2017;Fila et al, 2015;Ključnikov et al, 2019;Kurowska-Pysz et al, 2018;Meyer, D.F. et al, 2017;Niño-Amézquita et al, 2017).…”
Section: Introductionmentioning
confidence: 99%